2011
DOI: 10.1152/ajpendo.00490.2010
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids in the presence of high glucose amplify monocyte inflammation via Toll-like receptors

Abstract: Type 2 diabetes (T2DM) is characterized by hyperglycemia, dyslipidemia, and increased inflammation. Previously, we showed that high glucose (HG) induces Toll-like receptor (TLR) expression, activity, and inflammation via NF-B followed by cytokine release in vitro and in vivo. Here, we determined how HG-induced inflammation is affected by free fatty acids (FFA) in human monocytes. THP-1 monocytic cells, CD14 ϩ human monocytes, and transiently transfected HEK293 cells were exposed to various FFA (0 -500 M) and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(130 citation statements)
references
References 43 publications
8
116
1
5
Order By: Relevance
“…The concentration of palmitate required to elicit activation of macrophages is higher than that found during AT lipolysis [29,32]. Monounsaturated FAs do not stimulate TLR4-mediated activation of nuclear factor-κB (NF-κB) [29,33]. Unsaturated FAs have been shown to inhibit the LPS-induced NF-κB signalling pathway in macrophages [25,34].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of palmitate required to elicit activation of macrophages is higher than that found during AT lipolysis [29,32]. Monounsaturated FAs do not stimulate TLR4-mediated activation of nuclear factor-κB (NF-κB) [29,33]. Unsaturated FAs have been shown to inhibit the LPS-induced NF-κB signalling pathway in macrophages [25,34].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that palmitate induces ROS generation in various cells such as skeletal muscle cells [13], THP-1 monocytes [12], pancreatic islet cells [38], and adipocytes [39] mainly through the activation of the NADPH (nicotinamide adenine dinucleotide phosphate) oxidase system [12]; they may also be formed as by-products of mitochondrial oxidative phosphorylation [37]. These ROS stimulate JNK activation [28] and induce mitochondrial dysfunction [15].…”
Section: Discussionmentioning
confidence: 99%
“…Saturated, but not unsaturated, fatty acids have been shown to increase the expression of the inflammatory genes interleukin 1β, MCP-1, IL-6, and IL-8 in adipose tissue and liver [11,12]. To determine the effect of saturated and unsaturated fatty acids on gene expression in THP-1 macrophages, the cells were treated with different concentrations of saturated (palmitate or stearate) or unsaturated fatty acid (oleate) for 8 hours; and MIP-1 and IL-8 mRNA levels were measured using RT-PCR (Fig.…”
Section: The Effect Of Saturated and Unsaturated Fatty Acids On Mip-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple TLRs (TLR1-5, 7, and 9) are expressed on adipocytes, at least some of which appear to be functionally active [107][108][109][110]. High levels of free fatty acids from obesity and glucose from diabetes activate the innate immune system, with upregulated TLR expression that correlates with insulin resistance and increased inflammatory cytokine release in macrophages [111][112][113].…”
Section: Mechanism Of Association Between Ad and Metabolic Factorsmentioning
confidence: 99%